PENDEKATAN HERMENEUTIS DALAM PENGAJARAN HADITS: TELAAH METODOLOGI INTERPRETASI HADITS UNTUK PEMBELAJARAN KONTEMPORER - Katijah; Rasyidi (An-Nahdlah: Jurnal Pendidikan Islam, 2026)
Hadith instruction in Islamic education is still largely dominated by textual and normative approaches, which limit students’ contextual understanding and critical thinking skills. This study aims to analyze the characteristics of hermeneutical approaches in Hadith interpretation, to formulate a model for applying hermeneutics in Hadith instruction, and to examine its pedagogical implications for contemporary learning. This research employs a qualitative approach using library research methods, combined with hermeneutical, philosophical, and pedagogical analyses of recent Islamic and educational literature. The findings indicate that the hermeneutical approach emphasizes a dialogical relationship between the Hadith text, its historical context, and the reader’s horizon, enabling a more reflective and relevant understanding of Hadith. The application of hermeneutics in Hadith teaching can be operationalized through stages of pre-understanding, contextual analysis, dialogue between text and contemporary context, and critical reflection. Pedagogically, this approach implies a shift in learning objectives, dialogical teaching methods, and higher-order thinking-based assessment. This study contributes to the development of a contextual and adaptive model of Hadith instruction in contemporary Islamic education.